2021
DOI: 10.5812/aapm.113627
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dry Needling and Acupuncture in the Treatment of Neck Pain

Abstract: Context: Neck pain is a common phenomenon and affects a large segment of the population. Chronic neck pain, lasting more than 3 months, likely occurs in 10% - 30% of patients with acute neck pain and affects up to 288 million cases globally, carrying a significant cost in terms of quality of life, disability, and healthcare dollars. Here we review neck pain background, acupuncture and the evidence that exist to support acupuncture use in chronic neck pain. Results: Neck pain not only affects quality of life di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 85 publications
0
10
0
1
Order By: Relevance
“…Хорошие результаты дает сочетание этих методик с психотерапией. Акупунктура, инъекции в триггерные точки сухой иглой, тракционные и электростимуляционные методы требуют долгосрочных доказательных исследований [31][32][33][34][35][36]. Раннее начало мобилизационной физиотерапии и своевременное возвращение к нормальной физической активности считаются профилактикой хронизации болевого синдрома.…”
Section: терапия неспецифической цервикалгииunclassified
“…Хорошие результаты дает сочетание этих методик с психотерапией. Акупунктура, инъекции в триггерные точки сухой иглой, тракционные и электростимуляционные методы требуют долгосрочных доказательных исследований [31][32][33][34][35][36]. Раннее начало мобилизационной физиотерапии и своевременное возвращение к нормальной физической активности считаются профилактикой хронизации болевого синдрома.…”
Section: терапия неспецифической цервикалгииunclassified
“…The evidence for the clinical efficacy of acupuncture in the treatment of musculoskeletal (MSK) pain comes from the results of phase II and III clinical trials as well as smaller crossover and comparative studies 12,39,41,42,44,45,50,53,55 which are summarized in Table 1; it includes strong evidence to support acupuncture for use in both back 60 and neck pain. 61 Other clinical trials have been proposed or are currently being pursued for acupuncture and its efficacy in narrower clinical contexts such as cervical spondylosis, osteoporosis, spinal cord injury, or more specific control parameters. [47][48][49]51,56 A 2018 trial using electromyography and subjective pain outcomes found no significant difference between traditional and sham acupuncture.…”
Section: Acupuncture For Chronic Musculoskeletal Painmentioning
confidence: 99%
“…Interventional procedures vary by complexity and invasiveness, including trigger point injections, epidural steroid injections, sympathetic nerve blocks, radiofrequency ablation, cryoneuroablation, intrathecal drug delivery systems, and spinal cord stimulators, and deep brain stimulation ( 40 - 46 ). Although interventional therapies have associated risks, such as infection, dural puncture, spinal cord trauma, or nerve injury, the significant improvement in quality of life for certain patients makes them attractive treatment options, particularly in those who do not respond well to topical or oral analgesic agents ( 47 - 53 ).…”
Section: Evidence Acquisitionmentioning
confidence: 99%